2015
DOI: 10.5713/ajas.15.0552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Condensed Tannins in Mao (<i>Antidesma thwaitesianum</i> Muell. Arg.) Seed Meal on Rumen Fermentation Characteristics and Nitrogen Utilization in Goats

Abstract: Mao seed is a by-product of the wine and juice industry, which could be used in animal nutrition. The current study was designed to determine the effect of supplementation of mao (Antidesma thwaitesianum Muell. Arg.) seed meal (MOSM) containing condensed tannins (CT) on rumen fermentation, nitrogen (N) utilization and microbial protein synthesis in goats. Four crossbred (Thai Native×Anglo Nubian) goats with initial body weight (BW) 20±2 kg were randomly assigned to a 4×4 Latin square design. The four dietary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…There are reports indicating a decrease in methane production with the supplementation of plant containing condensed tannins and saponins (Poungchompu et al 2009;Wanapat et al 2014;Anantasook et al 2016;Gunun et al 2016). Supplementation of RPP at 16 mg reduced methane production in the present study.…”
Section: In Vitro Rumen Fermentation and Methane Productionmentioning
confidence: 51%
“…There are reports indicating a decrease in methane production with the supplementation of plant containing condensed tannins and saponins (Poungchompu et al 2009;Wanapat et al 2014;Anantasook et al 2016;Gunun et al 2016). Supplementation of RPP at 16 mg reduced methane production in the present study.…”
Section: In Vitro Rumen Fermentation and Methane Productionmentioning
confidence: 51%
“…Similarly, Gunun et al. () who reported that ruminal NH 3 ‐N concentrations were not affected by supplementation of mao seed meal (92 g SP/kg) at 0.8%–2.4% of total DM intake in goats.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, Gunun et al. () reported that ruminal NH 3 ‐N concentration at 0 and 4 hr postfeeding did not affected by supplementation of mao seed (96 g CT/kg) at 0.8%–2.4% of total DM intake in goats. This results different with our previous studies, could be due to the effects of CT on NH 3 ‐N concentrations vary with mao by‐product (mao pomace and mao seed), concentrations of CT, levels of supplementation and animals used.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations